Professional nurses' challenges regarding drug supply management in the primary health care clinics - Eleanor Mflathelwa Dube; Sibusiso Memory Zuma (Elsevier, 2022)
Drug Supply Management (DSM) is the core responsibility of pharmacists and pharmacist assistants however in practice South Africa has a huge shortage of pharmacists. In order to deal with excessive shortage of pharmacy personnel, the DSM responsibilities were handed over to professional nurses through strategies such as task shifting which were introduced as an alternative method to improve access to health care services especially in the Primary Health Care (PHC) clinics.The purpose of the study was to explore the challenges experienced by professional nurses regarding the implementation of the drug supply management standard operating procedure in the primary health care setting of the City of Ekurhuleni. The study was conducted in primary health care clinics in the City of Ekurhuleni. Method: An exploratory contextual qualitative research design was followed. The study population included all professional nurses working in the City of Ekurhuleni. Purposive sampling was used to select a sample of professional nurses with at least two years' experience. Semi-structured interviews were conducted. Data analysis was conducted and using qualitative content analysis. Results: The study identified the following challenges: non-adherence to the standard operating procedure for drug supply management, human resources challenges, inadequate management support and compromised patient care. Conclusion: The suggested recommendations from the study will promote adherence to the standard operation procedure regarding drug supply management outcomes.